Peningkatan Kemampuan Otomasi Perpustakaan bagi Pustakawan Madrasah di Provinsi Riau - Hadira Latiar; Nining Sudiar; Rosman H (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2022)
The madrasa library is a unit that supports learning and teaching activities, for that the library needs to provide various services that can be utilized by students and teachers. Based on the identification of problems with partners, there are several findings, namely; misunderstanding about library automation, lack of trained library staff, lack of support from the leadership, data input. Regarding the problems faced by partners, the team offers solutions to help solve these problems. The solution offered is in the form of technical guidance related to the implementation of library automation for madrasa librarians in Riau Province. The implementation of this service activity is packaged using a technical guidance approach. The activity was delivered using lecture methods, interactive discussions and practice. the results of the activities that have been carried out that all planned targets are achieved properly and in accordance with the program proposal. This activity received a positive response from partners and participants, seen from the enthusiasm of the participants in participating in the technical guidance activities. Furthermore, there was an increase in participants' understanding and skills in using Inlislite and SLiMS library application software. This indicator can be seen from the results of the pretest and posttest evaluations. While the main output of this activity is scientific articles that have been sent to online journals and the additional output is publication in online mass media.